Desain Dan Implementasi Aplikasi Penghafal Al-Quran Android Di Rumah Tahfidz Rabbunalloh Surabaya - Muhammad Ath Thariq Luqmana; Fidi Wincoko Putro; Mochammad Sholik (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
In general, some students also use a method called Tikrar, where the student repeats the verse. However, sometimes they're forgetting how many times it has been repeated. With Al-Quran Tikrar, there is a framework for memorizing Quran that can be found around the pages of the Quran. This helps to mark how many times the verse has been repeated using a ballpoint, pencil and such. But over time, the Quran would devreased its quality and condition, which causes the pages of the Quran seems dirty and damaged. The system works by making the memorizer or reciter be able to mark the number of times the verse has been repeated along with the level of fluency from "not yet memorized" to "mutqin" status, and the system can also store data on the quality of memorizing the Quran from day to day based on the number of verses memorized so that the supervisor or ustadz in the tahfidz Quran class can monitor the quality of the memorizer through the ustadz's dashboard. With Al-Quran Tikrar Android App, can memorize easily and integrated into Firebase so the repeated part can be recorded and not corrupted due to certain conditions.